NEOLOGISMS AND THEIR ROLE IN MODERN LEXICOGRAPHY - Roza Bahodirova; Lobar Baxodirova (TADQIQOTLAR, 2026)
Abstract Neologisms are newly created words, expressions, or meanings that appear in a language as society, technology, culture, and communication continue to develop. In lexicography, neologisms are important because dictionaries must constantly adapt to linguistic change and include new vocabulary used by speakers. This article discusses the concept of neologisms, their classifications, formation processes, and their significance in modern lexicography. The study also examines how lexicographers identify and record neologisms in dictionaries and how globalization, social media, and technological innovation contribute to lexical expansion. The article highlights the importance of neologisms in enriching language and reflecting social transformation.